LINGUISTIC AND PRAGMATIC FEATURES OF COMPLEX CONSTRUCTIONS IN ENGLISH AND UZBEK TEXTS (ILMIY TADQIQOTLAR VA YANGI OLAM, 2025)
Complex constructions serve as essential syntactic units that express hierarchical relations between propositions. This study examines the linguistic and pragmatic features of complex constructions in English and Uzbek texts, focusing on structural patterns, semantic functions, and discourse roles. Using a comparative-descriptive method supported by corpus-based examples, the research identifies several key contrasts between the two languages. English, as an analytical language, relies primarily on subordinating conjunctions, relative pronouns, and fixed word order; meanwhile, Uzbek employs morphological markers, participles, and flexible clause order due to its agglutinative nature. Pragmatically, both languages use complex constructions to convey coherence, emphasis, backgrounding, politeness, and textual organization. The study contributes to cross-linguistic syntactic theory and provides pedagogical insights for translation, teaching, and linguistic analysis.